The Dickensian Tropism in Contemporary Fiction - Georges Letissier (Cahiers Victoriens et Edouardiens)
Dickens is a prominent figure in neo-Victorian fiction. Indeed, ‘neo-Dickensian’ features as a sub-category of the neo-Victorian output and largely contributes to the so-called ‘Dickens Afterlife.’ Yet, studies of contemporary fictions overly drawing from Dickens’s works have so far been piecemeal as there has not been any attempt to address Dickensian rewritings from a wide, comprehensive perspective. It is our purpose in this paper to try to sketch out a few directions to (hopefully?) initiate an in-depth reflection on Dickens’s reception in the late twentieth and early twenty-first century from a sample of texts revisiting, recycling, ‘reprising’ or deconstructing their Dickensian hypotexts. This article draws from Jay Clayton’s study on Dickens and postmodernism to track down different contemporary responses from Kathy Acker to Sarah Waters and the Antipodean rewritings of both Peter Carey’s Jack Maggs and Lloyd Jones’s Mister Pip.